Evolution of interface character distribution in duplex stainless steel processed by cross-rolling and annealing. Issue 11 (November 2018) - Wang, Ming; Xu, Ting; Zhu, Yanli; Yin, Wenhong; Guo, Hong; Zhao, Ertuan; Fang, Xiaoying; Wang, Weiguo
Abstract: Duplex stainless steel UNS S31803 samples were cross-rolled with a true strain of ε  = 2 followed by annealing at 1323 K for 2 min and 240 min, respectively. The distributions of intervariant boundary planes in the precipitated austenite (A) from ferrite (F) and phase boundary planes conforming to Kurdjumov-Sache (K-S) orientation relationship (OR) were characterized by electron backscatter diffraction (EBSD) and the five-parameter analysis (FPA) method, respectively. The intervariant boundary planes with misorientation angle of 60° around <111> and <011> occur frequently and tend to terminate on the {111} plane. At the grain size level of 4 μm, the phase boundary appears to be connected with the K-S OR terminating on {110}F ‖{111}A at the early stage of annealing. When the grain size reaches approximately 20 μm, phase boundary was modified into {541}F ‖{533}A due to twinning in austenite during annealing.